2021
DOI: 10.3390/cancers13205232
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Fibrotic Tumor Microenvironment Regulates Anti-Tumor Immune Response

Abstract: High linear energy transfer (LET) radiation, such as neutron radiation, is considered more effective for the treatment of cancer than low LET radiation, such as X-rays. We previously reported that X-ray irradiation induced endothelial-to-mesenchymal transition (EndMT) and profibrotic changes, which contributed to the radioresistance of tumors. However, this effect was attenuated in tumors of endothelial-specific Trp53-knockout mice. Herein, we report that compared to X-ray irradiation, neutron radiation therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…H&E and Masson's Trichrome staining showed that irradiation increased skin inflammation, skin thickness, and collagen deposition, but these were significantly recovered by post-treatment with 2-ME after irradiation (Figure 2a). It is well known that a single dose of radiation higher than 10 Gy induces severe vascular damages [19]. Immunohistochemistry assay using CD31, an EC marker, showed that the vessel density of irradiated skin significantly decreased compared to that of nonirradiated skin, whereas 1 h before irradiation and 24 h after radiation, 2-ME treatment significantly inhibited the loss of microvessel density and the destruction of microvessels caused by irradiation (Figure 1b).…”
Section: -Me Repairs Radiation-induced Skin Vascular Damagementioning
confidence: 87%
“…H&E and Masson's Trichrome staining showed that irradiation increased skin inflammation, skin thickness, and collagen deposition, but these were significantly recovered by post-treatment with 2-ME after irradiation (Figure 2a). It is well known that a single dose of radiation higher than 10 Gy induces severe vascular damages [19]. Immunohistochemistry assay using CD31, an EC marker, showed that the vessel density of irradiated skin significantly decreased compared to that of nonirradiated skin, whereas 1 h before irradiation and 24 h after radiation, 2-ME treatment significantly inhibited the loss of microvessel density and the destruction of microvessels caused by irradiation (Figure 1b).…”
Section: -Me Repairs Radiation-induced Skin Vascular Damagementioning
confidence: 87%
“…Low-let radiation is oxygen dependent, and hypoxia can lead to radiation resistance. High LET radiation does not require oxygen and directly damages the DNA of tumor cells, which is more effective in killing tumor cells ( 52 ). Compared with HPV+ CC, HPV− CC is relatively more hypoxic.…”
Section: Hpv− Tumorsmentioning
confidence: 99%
“…For example, there are instances in which fractionated RT augments vessel permeability for extended periods by incremented ZO-1 and ICAM-1 expression on the endothelial surface [126]. Recent research points to high linear transfer energy (LET), such as neutron transfer, to present less pro-fibrotic and more pro-immunogenic properties than gamma ray-and X-ray-based RT approaches [127].…”
Section: Effects On Healthy Endothelial Cellsmentioning
confidence: 99%